DNA repair gene polymorphism is associated with the genetic basis of atherosclerotic coronary artery disease - Bazo, Ana Paula [UNESP]; Salvadori Jr., Décio; Salvadori, Ricardo A.F.; Sodré, Luciandro P. [UNESP]; Da Silva, Glenda N. [UNESP]; De Camargo, Elaine A. [UNESP]; Ribeiro, Lúcia Regina [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier, 2011)
Background: Atherosclerotic coronary artery disease (CAD) is a multifactorial process that appears to be caused by the interaction of environmental risk factors with multiple predisposing genes. It is nowadays accepted that increased levels of DNA damage induced by xenobiotics play an important role in the early phases of atherogenesis. Therefore, in this study, we focus on determining whether genetic variations in xenobiotic-metabolizing [glutathione-S-transferase theta 1 (GSTT1), glutathione-S-transferase mu 1 (GSTM1), cytochrome P450 IIEI (CYP2E1)] and DNA repair [X-ray cross-complementing group 1 (XRCC1)] genes might be associated with increased risk for CAD. Methods: A case-control study was conducted with 400 individuals who underwent subjected to coronary angiography. A total of 299 were patients diagnosed with effective coronary atherosclerosis (case group; >20% obstructive lesion), and 101 (control group) were individuals diagnosed as negative for CAD (<20% obstructive lesions). The polymorphism identifications for GSTM1 and GSTT1, and for CYP2E1 and XRCC1 genes were performed by polymerase chain reaction (PCR) amplification and by PCR-RFLP, respectively. Results and conclusions: The XRCC1 homozygous wild-type genotype Arg/Arg for codon 399 was statistically less pronounced in the case subjects (21.4%) than in controls (38.5%); individuals with the variant XRCC1 genotype had a 2.3-fold increased risk for coronary atherosclerosis than individuals with the wild-type genotype (OR=2.3, 95% CI=1.13-4.69). Conversely, no association between GSTM1, GSTT1, and CYP2E1gene polymorphisms and coronary atherosclerosis was detected. The results provide evidence of the role of DNA damage and repair in cardiovascular disease. © 2011 Elsevier Inc. All rights reserved.
Keywords: Atherosclerosis; CYP2E1; Gene polymorphisms; GSTM1; GSTT1; XRCC1; cytochrome P450 2E1; glutathione transferase M1; glutathione transferase T1; XRCC1 protein; adult; angiocardiography; cardiovascular risk; case control study; codon; controlled study; coronary artery atherosclerosis; DNA damage; DNA polymorphism; DNA repair; female; gene amplification; genetic association; genetic risk; genetic variability; homozygosity; human; major clinical study; male; polymerase chain reaction; priority journal; restriction fragment length polymorphism; sex difference; wild type; Aged; Alleles; Amino Acid Substitution; Case-Control Studies; Coronary Artery Disease; Cytochrome P-450 CYP2E1; DNA Damage; DNA Repair; DNA-Binding Proteins; Female; Gene Frequency; Genetic Predisposition to Disease; Glutathione Transferase; Humans; Male; Middle Aged; Polymorphism, Genetic